The geometry evolution of Early Paleozoic carbonate platform in the southwestern Tarim Basin, China: evidence from sequence stratigraphic analysis and seismic forward modeling - Jie Li; Jie Li; Zicheng Cao; Feng Geng; Suju Yang; Xuguang Sha; Mingjie Lan; Shenghou Wang; Yongchao Lu; Yangbo Lu; Daqing Tang; Zhao Zhang; et al. (Frontiers in Marine Science)
Deciphering the evolution of spatial geometry of carbonate platforms in deeply buried successions is still a challenge due to the low resolution of seismic data and the constraints of drilling wells. In this study, by combining a seismic forward model, we systematically delineated the external morphology and internal architecture of seismic reflection and established a depositional model of a carbonate platform. The Lower Paleozoic strata display the high-amplitude reflection in the Lower-Middle Cambrian interval and the low-amplitude reflection in the Upper Cambrian-Middle Ordovician interval. The high-amplitude reflection interval thins or wedges out towards the center of the present Southwest Depression section, and thickens to the north and south. Inside of the high-amplitude interval, the seismic reflection terminated at the top reflector. Seismic forward modeling was performed to examine the validity of possible hypothetical models in the studied area. The modeling results show that the simulated stratigraphic patterns are comparable to a ramp or depression geometry which is well fit to the characteristics of actual seismic reflections. Such a ramp or depression geometry is built upon the changes in sea level and climate during the Cambrian period. This study emphasizes the potential of the integration of sequence stratigraphic analyses and seismic forward modeling as a seismic workflow for retrieving the stratigraphic architecture and platform geometry.